2012
DOI: 10.1590/s0101-20612012005000096
|View full text |Cite
|
Sign up to set email alerts
|

Application of roasted rice bran in cereal bars

Abstract: The objective of this study was to evaluate the viability of using microwave-roasted rice bran as an ingredient in high-fiber cereal bars to obtain a product with good acceptability. The influence of the rice flakes, corn flakes, and roasted rice bran levels on the physical and chemical characteristics of the cereal bars was studied. The overall acceptability of three selected formulations was also evaluated. An increase in the roasted rice bran level in the formulation reduced the force of rupture and water a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
3
9
1
3
Order By: Relevance
“…It can be observed that the results are well above the most cited by several authors [Mourão et al (2009) reducing sugars, the formulations were statistically different (p ≤ 0.05) ranging from 5.17% (formulation 11) to 6.22% (formulation 5). Due to the presence of sorbitol in place of glucose syrup in these formulations the results of this study are much lower than those found by Garcia et al (1998) who obtained for reducing sugars values between 23.31 to 25.39% due to the high percentage of glucose syrup used in the formulations.…”
Section: Resultscontrasting
confidence: 87%
See 3 more Smart Citations
“…It can be observed that the results are well above the most cited by several authors [Mourão et al (2009) reducing sugars, the formulations were statistically different (p ≤ 0.05) ranging from 5.17% (formulation 11) to 6.22% (formulation 5). Due to the presence of sorbitol in place of glucose syrup in these formulations the results of this study are much lower than those found by Garcia et al (1998) who obtained for reducing sugars values between 23.31 to 25.39% due to the high percentage of glucose syrup used in the formulations.…”
Section: Resultscontrasting
confidence: 87%
“…Moreover, Garcia et al (1998) found ash values between 2.61 and 3.68%, up from values found in this study.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The presence of rice flakes made the bars more similar to commercial cereal bars, since this ingredient is commonly used for this type of product, and may have thus increased the cereal bars acceptability (Fig. A) . The positive effect of the mixture of the three components in the sensory acceptability may be related to the fact that cereal bars are formulated with a mixture of various dry ingredients (such as rice flakes, oats, dried fruit) and binders (such as glucose syrup and honey) suggesting that banana peel flour is a potential ingredient to be used in cereal bars .…”
Section: Resultsmentioning
confidence: 99%